Fruity Cafe / Muhammad Rizanizam Abd. Hamid ... [et al.] - Abd.Hamid, Muhammad Rizanizam; Senapi, Mohamad Fauzan; Mar'ie, Rahmasari; Mohd.Nor, Noor Shuhada; Abd Jabbar, Badrul Hizar; Ahmad, Zulkifli (Malaysian Entrepreneurship Development Centre (MEDEC), 2002)
In Malaysia, there are lots of cafe had been set up by Malaysians or by foreigners. Based on the surveys that we had done, we can conclude that Malaysians nowadays, love to spend 2/5 hours of their days on cafes. It will be about 3 to 4 hours. This phenomenon brings us to make this kind of business. This cafe named Fruity Cafe.